2010
DOI: 10.7150/ijms.7.251
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal siRNA against Toll-like receptor 4 reduces nociception in a rat model of neuropathic pain

Abstract: Background: Neuropathic pain is characterized by hyperalgesia, allodynia and spontaneous pain. It often occurs as a result of injury to peripheral nerves, dorsal root ganglions (DRG), spinal cord, or brain. Recent studies have suggested that Toll-like receptor 4 (TLR4) might play a role in neuropathic pain. Methodology/Principal Findings: In this study, we investigated the role of TLR4 in a rat chronic constriction injury (CCI) model and explored the feasibility of treating neuropathic pain by inhibiting TLR4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 46 publications
4
69
0
Order By: Relevance
“…This work has been further replicated by laboratories world wide, demonstrating the key role of TLR4 in several preclinical models of neuropathic pain (Lan et al, 2010; Wu et al, 2010). Lan et al (2010) showed that TLR4 small interfering RNA (siRNA) administered intrathecally in rats prior to the development of allodynia induced with a bone cancer pain model displayed significantly attenuated behavioral hypersensitivity and decreased expression of spinal microglial markers and proinflammatory cytokines.…”
Section: Toll-like Receptors and Painmentioning
confidence: 76%
“…This work has been further replicated by laboratories world wide, demonstrating the key role of TLR4 in several preclinical models of neuropathic pain (Lan et al, 2010; Wu et al, 2010). Lan et al (2010) showed that TLR4 small interfering RNA (siRNA) administered intrathecally in rats prior to the development of allodynia induced with a bone cancer pain model displayed significantly attenuated behavioral hypersensitivity and decreased expression of spinal microglial markers and proinflammatory cytokines.…”
Section: Toll-like Receptors and Painmentioning
confidence: 76%
“…Moreover, TLR signaling was also involved in neuroinflammation [158], since suppression of TLR4 by intrathecally administered siRNA could reduce neuropathic pain [159], while activation of TLR9 by intracerebroventricular administration of CpG might be an effective therapeutic strategy for Alzheimer's disease [160].…”
Section: Other Pulmonary and Neurological Diseasesmentioning
confidence: 99%
“…1 for summary). Furthermore, TLR4 blockade not only prevents the initial development of neuropathic pain (Tanga et al, 2005) but also reverses established neuropathic pain (Bettoni et al, 2008;Hutchinson et al, 2008c;Cao et al, 2009;Lan et al, 2010;Liu et al, 2010a;Saito et al, 2010;Wu et al, 2010). The nociceptive consequences of TLR4-induced central immune signaling are due, at least in part, to p38-dependent activation of reactive glial phenotypes (Liu et al, 2010a) and up-regulation of prosta-NEUROIMMUNOPHARMACOLOGIC IMPLICATIONS FOR OPIOID ANALGESIA glandin E2 and TNF-␣ (Saito et al, 2010).…”
Section: What Is the Impact Of The Central Immunementioning
confidence: 99%